Circulating prolactin and breast cancer risk among pre- and postmenopausal women in the EPIC cohort. - Tikk, K; Sookthai, D; Johnson, T; Rinaldi, S; Romieu, I; Tjønneland, A; Olsen, A; Overvad, K; Clavel-Chapelon, F; Baglietto, L; Boeing, H; Trichopoulou, A; et al. (Oxford University Press, 2014)
BACKGROUND: Experimental and epidemiological evidence suggests that prolactin might play a role in the etiology of breast cancer. We analyzed the relationship of prediagnostic circulating prolactin levels with the risk of breast cancer by menopausal status, use of postmenopausal hormone replacement therapy (HRT) at blood donation, and by estrogen and progesterone receptor status of the breast tumors. PATIENTS AND METHODS: Conditional logistic regression was used to analyze the data from a case-control study nested within the prospective European EPIC cohort, including 2250 invasive breast cancer and their matched control subjects. RESULTS: Statistically significant heterogeneity in the association of prolactin levels with breast cancer risk between women who were either pre- or postmenopausal at the time of blood donation was observed (Phet = 0.04). Higher serum levels of prolactin were associated with significant increase in the risk of breast cancer among postmenopausal women [odds ratio (OR)Q4-Q1 = 1.29 (95% confidence interval, CI, 1.05-1.58), Ptrend = 0.09]; however, this increase in risk seemed to be confined to women who used postmenopausal HRT at blood donation [ORQ4-Q1 = 1.45 (95% CI 1.08-1.95), Ptrend = 0.01], whereas no statistically significant association was found for the non-users of HRT [ORQ4-Q1 = 1.11 (95%CI 0.83-1.49), Ptrend = 0.80] (Phet = 0.08). Among premenopausal women, a statistically non-significant inverse association was observed [ORQ4-Q1 = 0.70 (95% CI 0.48-1.03), Ptrend = 0.16]. There was no heterogeneity in the prolactin-breast cancer association by hormone receptor status of the tumor. CONCLUSION: Our study indicates that higher circulating levels of prolactin among the postmenopausal HRT users at baseline may be associated with increased breast cancer risk.